Roadmap for creating an accelerated three-year medical education program. Issue 1 (1st January 2017) - Leong, Shou Ling; Cangiarella, Joan; Fancher, Tonya; Dodson, Lisa; Grochowski, Colleen; Harnik, Vicky; Hustedde, Carol; Jones, Betsy; Kelly, Christina; Macerollo, Allison; Reboli, Annette C.; Rosenfeld, Melvin; et al.
ABSTRACT: Medical education is undergoing significant transformation. Many medical schools are moving away from the concept of seat time to competency-based education and introducing flexibility in the curriculum that allows individualization. In response to rising student debt and the anticipated physician shortage, 35% of US medical schools are considering the development of accelerated pathways. The roadmap described in this paper is grounded in the experiences of the Consortium of Accelerated Medical Pathway Programs (CAMPP) members in the development, implementation, and evaluation of one type of accelerated pathway: the three-year MD program. Strategies include developing a mission that guides curricular development – meeting regulatory requirements, attaining institutional buy-in and resources necessary to support the programs, including student assessment and mentoring – and program evaluation. Accelerated programs offer opportunities to innovate and integrate a mission benefitting students and the public. Abbreviations : CAMPP: Consortium of accelerated medical pathway programs; GME: Graduate medical education; LCME: Liaison committee on medical education; NRMP: National residency matching program; UME: Undergraduate medical education